Are rankings relevant at all? - Abd Razak, Dzulkifli (2010)
FIVE Malaysian universities were ranked among the top institutions in the 2010 QS Asian University Rankings. While some cheered and reckoned this is deservedly so considering the hard work others felt it is about time. At Universiti Sains Malaysia (USM), however, most were amused by the news for the simple reason that they have neither agreed to the invitation to participate nor have they submitted any data or information. Nevertheless, USM has been assigned a meaningless "number".